Accreditation Policy and Internal Quality Assurance: A Study of Private Islamic Religious Universities in Nusa Tenggara - Winengan Winengan; Safwira Guna Putra (Journal of Enterprise and Development (JED), 2025)
Purpose: This study aims to investigate the implementation of the Internal Quality Assurance System at Private Islamic Religious Universities in the Nusa Tenggara region, specifically focusing on institutions that have not yet attained the minimum required accreditation ratings. Additionally, it seeks to identify the key factors that impede the effectiveness of internal quality assurance initiatives.Method: This research employs a qualitative field study approach. Data were collected through interviews, observations, and document analysis involving participants from six selected institutions, including university leaders and managers of internal quality assurance units. Data analysis was conducted concurrently, utilizing an interactive model work system. The validity of the data was assessed through credibility tests, which were implemented by extending the research duration, enhancing observation persistence, and employing triangulation methods.Result: The implementation of the internal quality assurance system is currently inadequate and primarily motivated by accreditation requirements rather than by a commitment to continuous quality improvement. Most institutions are deficient in establishing comprehensive quality assurance frameworks, maintaining proper documentation, and fostering a robust quality culture, which can be attributed to limited resources, inadequate planning, and insufficient understanding among leadership. Consequently, many institutions struggle to meet accreditation standards. To enhance their effectiveness, these institutions must fortify their internal quality assurance systems through consistent planning, leadership commitment, and support from their coordinating bodies for private sector universities to ensure sustainable quality in higher education.Practical Implications for Economic Growth and Development: This study serves as a valuable reference for the development of a more effective quality management system in university governance, aligned with the National Standards of Higher Education and responsive to the evolving demands of society. By implementing sound governance practices, institutions can ensure the delivery of quality education, ultimately producing competent graduates who are well-equipped to meet the needs of the business and industrial sectors.